Political Discourse and Moral Negotiations of the Tarbiyah Movement among Students: An Active Reception Analysis of LDK and KAMMI Students at UIN Jakarta - Andi Fakhrullah; Andi M. Faisal Bakti (Fakultas Ushuluddin Adab dan Dakwah UIN Sultanah Nahrasiyah Lhokseumawe, 2026)
This study examines how students negotiate the political discourse and moral standards promoted by the Tarbiyah Movement at UIN Syarif Hidayatullah Jakarta. Although previous studies have primarily focused on the ideological and organizational dimensions of the movement, limited attention has been paid to how students at Islamic higher education institutions actively interpret its messages. Drawing on Stuart Hall’s encoding/decoding theory and the active reception perspective, this study employs a qualitative phenomenological approach. Data were collected through in-depth interviews and non-participant observation involving members of the Syahid Campus Da’wah Institute (LDK) and the Indonesian Muslim Students Association (KAMMI) during the 2020–2024 period. The findings indicate that students are an active audience, not passive recipients, of Tarbiyah discourse. Participants demonstrated dominant, negotiated, and oppositional readings of political and moral messages. Dominant readings emerged when Tarbiyah narratives aligned with participants’ religious beliefs and identity orientations, particularly regarding Islamic dress codes. Conversely, negotiated and oppositional interpretations are more evident in relation to political affiliation with PKS, the relationship between religion and the state, and smoking bans. This study concludes that the reception of Tarbiyah discourse is selective, issue-specific, and shaped by students’ religious backgrounds, organizational affiliations, and personal experiences.